1998
DOI: 10.1177/019262339802600412
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations of the c-H-ras Gene in Spontaneous Liver Tumors of Transgenic Mice Carrying the Human c-H-ras Gene

Abstract: Spontaneous proliferative liver lesions were found in 15 (13 males and 2 females) of 244 (122 of each sex) transgenic (Tg) mice carrying the human prototype c-H-rus gene (msH2). The liver lesions included 3 foci of cellular alteration, 1 hcpatocellular adenoma, 5 hepatocellular carcinomas. and 4 hepatic hemangiosarcomas in the males and 1 focus of cellular alteration and 1 hepatocellular carcinoma in the females. The mutation patterns of the human and endogenous mouse c-H-rus codon 61 in these proliferative li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…With regard to the mechanism on the tumorigenesis in rasH2 mice, as reported in the previous studies [45][46][47][48][49][50][51] , somatic mutations of codon-12, -13, and -61 of c-Ha-ras transgene were detected in spontaneous or chemically induced tumors in rasH2 mice. However, the incidences of point mutations of the transgene appeared to vary in tumors of rasH2 mice, and some carcinogens induced extremely low incidences of transgene mutations 45,52,53 .…”
Section: Discussionmentioning
confidence: 80%
“…With regard to the mechanism on the tumorigenesis in rasH2 mice, as reported in the previous studies [45][46][47][48][49][50][51] , somatic mutations of codon-12, -13, and -61 of c-Ha-ras transgene were detected in spontaneous or chemically induced tumors in rasH2 mice. However, the incidences of point mutations of the transgene appeared to vary in tumors of rasH2 mice, and some carcinogens induced extremely low incidences of transgene mutations 45,52,53 .…”
Section: Discussionmentioning
confidence: 80%
“…These data may suggest a possible functional disorder of the cell cycle only in the uterine epithelium of rasH2 mice. However, with regard to the enhanced carcinogenesis in various organs of rasH2 mice treated with genotoxic carcinogens, it has been reported that somatic mutations of codons 12, 13 and 61 of the c-Ha-ras transgene were detected in spontaneous or chemically induced tumors in rasH2 mice [21][22][23][24][25][26][27] . On the other hand, the incidences of point mutations of the transgene appeared to vary in tumors of rasH2 mice, and some carcinogens induced extremely low incidences of transgene mutations 21,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, his group suggested that definite somatic point mutation of the human c-Ha-ras transgenes in certain cell types may be a causative event in tumorigenesis in these transgenic mice. Hayashi et al (1998) performed mutation analyses (DNA amplification using polymerase chain reaction, single-strand conformation polymorphism (PCR- The liver lesions included 3 foci of cellular alteration, 1 hepatocellular adenoma, 5 hepatocellular carcinomas, and 4 hepatic hemangiosarcomas in males and 1 focus of cellular alteration and 1 hepatocellular carcinoma in females. The hepatocellular carcinomas in 4 males and 1 female contained a point mutation in the mouse c-Ha-ras gene: 3, 1, and 1 carcinomas had a CAA to AAA transversion at the first base of codon 61, a CAA to CTA transversions, and a CAA to CGA transition at the second base of codon 61, respectively (Table 2).…”
Section: Molecular Analyses Of Spontaneous Tumors In Rash2 Micementioning
confidence: 99%
“…No mutations in human or mouse c-Ha-ras codon 61 were detected in altered cell foci or hepatocellular adenomas. Based on these results, Hayashi et al (1998) pointed out that spontaneous liver tumors in rasH2 Tg mice contain different mutation patterns depending on the histologic type or cell origin of the tumors (i.e., hepatocellular carcinomas or hepatic hemangiosacomas). The mutation patterns of the human c-Ha-ras codon 61 and endogenous mouse c-Ki-ras codons 12, 13, and 61 in spontaneous lung proliferative lesions [3 bronchiolo-alveolar hyperplasias (BAHs), 2 bronchiolo-alveolar adenomas (BAAs), and 5 bronchiolo-alveolar adenocarcinomas (BACs)] observed in 10 of 244 rasH2 mice have been analyzed by DNA amplification using polymerase chain reaction, single-strand conformation polymorphism (PCR-SSCP), and oligonucleotide dot blot hybridization (Mori et al, 2000).…”
Section: Molecular Analyses Of Spontaneous Tumors In Rash2 Micementioning
confidence: 99%